IS ARBITRAGE PRICING THEORY IS A FAIRY TALE ?: THE EVIDENCE FROM INDONESIA WITH ORDINARY LEAST SQUARE ESTIMATION - Reza, Faizal; Nurqamarani, Adisthy Shabrina; Solihin, Danna (RJABM (Research Journal of Accounting and Business Management), 2018)
Time series analysis in financial sector has grown in popularity since the last few decades, theories about capital markets are increasingly studied since Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) are often compared and paired with one another. The development of APT is widespread by involving many macroeconomic variables. Unfortunately there is no consensus until now. This paper aims to examine the relevance of APT in the case of Indonesia during the period 2009-2017 with standard multiple regression equations. From three independent variables, only exchange rates have a significant influence on the composite stock price (IHSG) in Indonesia, while inflation and GDP have no significant effect on stock prices. 99.8% variation in stock price formation can be explained by independent variables where there is a positive relationship between exchange rate and stock price indicates a mechanism of stock price formation through strong domestic demand before fourth quarter 2016 and trade effect (export-import) after fourth quarter 2016 .